Evaluating reliability and validity of the modified radiographic union scale for tibia (mRUST) among North American and Tanzanian surgeons - Coburn, Alexander (OTA Int, 2020)
OBJECTIVES: To determine the international reliability and validity of the modified Radiographic Union Scale for Tibial fracture (mRUST) scoring method for open tibial shaft fractures based on ratings of radiographs by separate groups of North American and Tanzanian surgeons. METHODS: Seven North American and 9 Tanzanian surgeons viewed 100 pairs of AP and lateral radiographs of open tibial shaft fractures obtained in Dar Es Salaam, Tanzania. The radiographs showed 25 patients’ fractures at 4 time points postfracture after treatment with either external fixation or intramedullary nailing. Surgeons evaluated each fracture using the mRUST scoring method and indicated their confidence that the fracture was healed on a scale from 1 to 10. Reliability of mRUST was determined using inter-rater agreement among North American and Tanzanian surgeons. Validity was determined via analysis of correlation between mRUST scores and EQ-5D-3L index scores at each time point postfracture. RESULTS: mRUST scores demonstrated strong reliability overall (ICC = 0.64) as well as within each group of North American (ICC = 0.72) and Tanzanian (ICC = 0.69) surgeons. Reliability was stronger for external fixation than for intramedullary nailing cases. mRUST scores were significantly correlated with overall healing confidence at all time points and with quality of life at 6 months and 1 year postfracture. mRUST scores also correlated significantly with patients’ quality of life scores (EQ-5D index) at 6 months and 1 year postfracture. CONCLUSION: North American and Tanzanian surgeons exhibited strong agreement in rating open tibial shaft fractures. Using mRUST scores is a valid means of assessing radiographic healing of tibial fractures in austere environments like Tanzania.